Audit Planning and Performance of Local Governments in Uganda: A Case Study of Mbale City Council - Anselm Benard Okumu (Uganda Christian University, 2024)
The study on audit planning and performance within Mbale City Council local government in Uganda employed a quantitative research design, involving a population of 40 individuals, from which a sample of 36 respondents was selected using Solomon's formula (1960). The research aimed to investigate three specific objectives: the impact of audit strategy, audit risk, and audit checklists on the performance of the local government. Findings highlighted that audit strategy significantly influences the overall performance of Mbale City Council by aligning organizational activities with strategic goals, thereby enhancing operational efficiency and accountability. Additionally, the study revealed that managing audit risks is pivotal for maintaining optimal performance levels; identifying and mitigating risks through structured audit processes enables the council to better navigate challenges and improve service delivery. The importance of audit checklists in enhancing performance outcomes was also emphasized, as comprehensive checklists ensure systematic review and address all critical audit tasks, promoting consistency and thoroughness. The study's recommendations advocate for the adoption of tailored audit strategies aligned with Mbale City Council's specific objectives and operational contexts, and the integration of robust risk assessment frameworks into audit planning to proactively manage potential performance obstacles. In conclusion, the study underscores the significance of effective audit management practices in local government settings like Mbale City Council, suggesting that implementing these recommendations can optimize performance, enhance service delivery, and foster greater accountability and transparency in operations. These findings contribute to the broader understanding of audit planning's role in improving organizational performance within public sector entities.
Undergraduate Research